2017
DOI: 10.1093/nar/gkx893
|View full text |Cite
|
Sign up to set email alerts
|

ClusterCAD: a computational platform for type I modular polyketide synthase design

Abstract: ClusterCAD is a web-based toolkit designed to leverage the collinear structure and deterministic logic of type I modular polyketide synthases (PKSs) for synthetic biology applications. The unique organization of these megasynthases, combined with the diversity of their catalytic domain building blocks, has fueled an interest in harnessing the biosynthetic potential of PKSs for the microbial production of both novel natural product analogs and industrially relevant small molecules. However, a limited theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Failed production, reduced yield, and loss of product fidelity remain major challenges in PKS engineering. Online database tools such as ClusterCad (Eng et al, 2018) and SBSPKS (Khater et al 2017) can facilitate PKS engineering, which can minimize the risk of failed production. A larger challenge is to increase fidelity and improve yield in multimodular systems, particularly as these systems are more likely to lose product fidelity as there is an added variable of intermodular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Failed production, reduced yield, and loss of product fidelity remain major challenges in PKS engineering. Online database tools such as ClusterCad (Eng et al, 2018) and SBSPKS (Khater et al 2017) can facilitate PKS engineering, which can minimize the risk of failed production. A larger challenge is to increase fidelity and improve yield in multimodular systems, particularly as these systems are more likely to lose product fidelity as there is an added variable of intermodular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Even worse from a perspective of simple mix-andmatch eingeering approaches, it appears that a cumulated effect and a non-intuitive interplay of the identity of both ACP and substrate influence the turnover of many downstream modules. Future engineering strategies are likely to be more successful by either retaining substrate specificities, 43 or by preserving the natural domain-domain interfaces, [44][45][46][47] a task that might be achieved with the support from evolutionary analysis. 48 Plasmids: Plasmids harboring genes encoding individual PKS modules were either generated in this study via In-Fusion Cloning (Takara), site directed mutagenesis, or reported previously.…”
Section: (Iii)mentioning
confidence: 99%
“…Currently, homology tools such as BLAST 126 and HMMer 127 are largely employed to extract these elements, but steps toward automated identication of useful elements based on a (desired) chemical structure are being employed. Clus-terCAD 117 is one such tool that focuses on cataloging and highlighting of PKS elements (collected from MIBiG), with the ultimate goal of de novo design of clusters. In addition to identifying the best starting BGC most similar to a desired structure, ClusterCAD aims to identify a parsimonious number of domain swaps, deletions and additions based on sequence homology to known clusters.…”
Section: Toward Automated Cluster Designmentioning
confidence: 99%